Mechanisms by which chloropicrin fumigation promotes soil potassium conversion and absorption - Sun, Yang; Zeng, Rong; Fang, Wensheng; Hua, Jvling; Huang, Shuijin; Wang, Qiuxia; Cao, Aocheng; Zhu, Feng; Zhang, Haiyan (Frontiers in Microbiology, 2023)
Fumigation of soil using chloropicrin has been proven to significantly affect soil nutrient cycling, but the mechanism by which soil potassium conversion and plant uptake is promoted remains unclear. In this study, we conducted a fumigation experiment to investigate the effects of chloropicrin soil fumigation on the conversion of soil potassium post-fumigation (days 7-70), and its mechanisms, tomatos were planted in fumigated and non-fumigated soils to enable further comparisons. Resultsshowed that the content of rapidly available potassium and available potassium decreased by 16%-24% and 17%-23% at day 28 respectively, when tomato was planted in chloropicrin-fumigated soils compared to the non-fumigated soils. The potassium content of tomato planted in fumigated soil was significantly higher than that planted in non-fumigated soil (30.3 vs. 21.9 mg g −1 dry weight). Chloropicrin fumigation resulted in a significant change in the soil bacterial and fungal community structures, and trigged a long-term (at least 70-day) decrease in microbial diversity. Network analysis showed that chloropicrin soil fumigation changed microbial co-occurrence patterns by decreasing bacterial total links, nodes, and average degree, and increasing fungal total links, nodes, and average degree. Chloropicrin fumigation caused significant changes in the relative abundance of Bacillus species, which are involved in 2 potassium dissolution. Structural equation model (SEM) suggested that fumigation with chloropicrin enhanced the contribution of soil potassium to tomato growth and reduced the contribution of bacterial communities. Together, the results of our study help in understanding the crop yield enhancement mechanism of soil fumigation.